Gloves, an educational technology assisting the adherence of nursing professionals to contact precautions: a methodological study - Jovíria Márcia Ferreira de Oliveira Padilha (Online Brazilian Journal of Nursing, 2013)
This is a dissertation project that is part of the Professional Master’s Program in Assisting Nursing of Fluminense Federal University. Aim: To propose an educational technology in a CD-ROM (video) format, aiming to encourage nursing professionals to adhere to contact precautions, with a focus on gloves. Method: This is a methodological study, which adopts a quantitative-qualitative approach, that is done in four steps: designing a CD-ROM, validation of the media, selection of the target audience and adequacy of the media. The data collection was done through interviews and the use of evaluation instruments. The sample consisted of nursing professionals and expert judges. Subjects are nursing professionals from medical and surgical clinics of a College Hospital in the state of Rio de Janeiro. Expected results: this research is in progress. It is expected to contribute to improving the assistance provided and a higher adherence to contact precautions on the part of nursing teams.